ANALISIS PENGARUH CSR TERHADAP CORPORATE REPUTATION DAN BRAND AWARENESS BANK MANDIRI (Studi pada Mahasiswa Undip Semarang) - Ayu, Elva Putri Kusumaning; Kusumawardhani, Amie (Diponegoro Journal of Management, 2015)
The purpose of every business is not only looking for a sustainable profit, but alsoto develop the society, including in universities. This purpose can be achieved by implementing social responsibility. Therefore, the aim of this study is to analyze the effect of corporate social responsibility (CSR) on brand awareness through company reputation of Mandiri Bank.Population  of  this  study  is  Diponegoro  University  students  who  have  saving account at Mandiri Bank. As many as 108 respondents were tahen as sample in this study. Structural Equation Modeling (SEM) was applied in this study and AMOS version 21.0 was used to analyze data.The  study  found  that  corporate social  responsibility  has  a  direct  positive  and significant  effect on brand awareness. Furthermore, the result  also showed that  CSR affects brand awareness indirectly thourgh corporate reputation.